2015
DOI: 10.3109/03008207.2015.1045065
|View full text |Cite
|
Sign up to set email alerts
|

Expression of thrombospondin-1 by tumor cells in patient-derived ovarian carcinoma xenografts

Abstract: Ovarian carcinoma PDX are a useful tool to investigate the relative contribution of stroma and tumor cells in the production of tumor associated factors, in relation to the tumor behavior, molecular properties and response to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…TSP-1 was also reported to contribute to metastatic spread by promoting tumor cell emboli formation ( Incardona et al, 1995 ). In recent years, an increasing number of studies have tended to present TSP-1 as a poor prognosis and recurrence marker in many cancer types including glioma ( Perez-Janices et al, 2015 ), melanoma ( Borsotti et al, 2015 ) as well as ovarian and pancreatic carcinomas ( Lyu et al, 2013 ; Nie et al, 2014 ; Pinessi et al, 2015 ). Among TSP-1 ligands, CD36 and CD47 cell-surface receptors act as key integrators of multiple signals regulating tumor growth and dissemination both positively and negatively.…”
Section: Tsp-1: a Main Actor Within Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…TSP-1 was also reported to contribute to metastatic spread by promoting tumor cell emboli formation ( Incardona et al, 1995 ). In recent years, an increasing number of studies have tended to present TSP-1 as a poor prognosis and recurrence marker in many cancer types including glioma ( Perez-Janices et al, 2015 ), melanoma ( Borsotti et al, 2015 ) as well as ovarian and pancreatic carcinomas ( Lyu et al, 2013 ; Nie et al, 2014 ; Pinessi et al, 2015 ). Among TSP-1 ligands, CD36 and CD47 cell-surface receptors act as key integrators of multiple signals regulating tumor growth and dissemination both positively and negatively.…”
Section: Tsp-1: a Main Actor Within Tumor Microenvironmentmentioning
confidence: 99%
“…Indeed, its ability to interact with multiple ligands enables TSP-1 to regulate a wide range of processes such as tumor cell adhesion ( Li et al, 2006 ), proliferation ( Sick et al, 2011 ), survival or apoptosis ( Manna and Frazier, 2004 ; Saumet et al, 2005 ; Rath et al, 2006a , b ), tumor invasion and metastatic dissemination ( Jayachandran et al, 2014 ; Borsotti et al, 2015 ), inflammation, immune response ( Grimbert et al, 2006 ) and response to treatment ( Lih et al, 2006 ; Bi et al, 2014 ). Such pleiotropic effects may be governed by TSP-1 concentration as well as by its origin, whether it originates from tumor cells or the stroma compartment ( Pinessi et al, 2015 ). Reverse responses may also be observed depending on the cancer type.…”
Section: Tsp-1: a Main Actor Within Tumor Microenvironmentmentioning
confidence: 99%
“…It was revealed that desmin and H-caldesmon proteins were expressed in 8 models among 10 leiomyosarcomas PDX models, and the changes in vimentin and cytokeratin expression in carcinosarcomas PDX models varied over the generations [37]. Another related evidence revealed that thrombospondin-1 (TSP-1), regulating cell interaction with the microenvironment, was expressed in 10/11 ovarian cancer PDXs and upregulated in the homologous primary tumor, implying similar microenvironment of the PDX and original tumor [47]. On the other hand, it is also critical to illustrate the nonhuman component of expression data in PDX models.…”
Section: Phenotypic and Proteomic Featuresmentioning
confidence: 96%
“…MYC is involved in cellular differentiation, growth and apoptosis, and plays a role in various human cancers [ 93 ]. The upregulation of the miR-17-92 cluster is associated with the downregulation of thrombospondin 1 (THBS1), an adhesive glycoprotein, which mediates cell–matrix and cell–cell interactions, with the potential to inhibit angiogenesis [ 94 ]. Therefore, the miR-17-92 cluster could be therapeutically targeted to lessen angiogenetic tumour growth in MYC-positive angiosarcomas.…”
Section: Micrornas In Human Soft Tissue Sarcomamentioning
confidence: 99%